2021
DOI: 10.3390/pharmaceutics13020191
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone Nanoparticles as Promising Candidates for Nanocarriers in Novel Nanomedicines

Abstract: An investigation of the interactions between bio-polymeric nanoparticles (NPs) and the RAW 264.7 mouse murine macrophage cell line has been presented. The cell viability, immunological response, and endocytosis efficiency of NPs were studied. Biopolymeric NPs were synthesized from a nanoemulsion using the phase inversion composition (PIC) technique. The two types of biopolymeric NPs that were obtained consisted of a biocompatible polymer, polycaprolactone (PCL), either with or without its copolymer with poly(e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…No cytotoxic effects of the particles were found within a 5 h incubation as shown in the SI (Figure S2) . These results were in agreement with previous studies that demonstrated PCL NPs to be biocompatible [ 40 , 41 ]. Considering their good biocompatibility, all PCL[BRP-187] particles as well as the free drug were studied for their efficiency to inhibit the drug target FLAP in PMNL and, thus, to prevent 5-LO product formation [ 42 ].…”
Section: Resultssupporting
confidence: 93%
“…No cytotoxic effects of the particles were found within a 5 h incubation as shown in the SI (Figure S2) . These results were in agreement with previous studies that demonstrated PCL NPs to be biocompatible [ 40 , 41 ]. Considering their good biocompatibility, all PCL[BRP-187] particles as well as the free drug were studied for their efficiency to inhibit the drug target FLAP in PMNL and, thus, to prevent 5-LO product formation [ 42 ].…”
Section: Resultssupporting
confidence: 93%
“…7 A–I). As a follow up to these results, we evaluated if other polymorphic nanoparticles such as PEG-PLGA and PCL can suppress Aβ 1–42 aggregation [ 56 , 57 ]. For this experiment we used 5 µM PEG-PLGA and 100 nM PCL as they were found to protect neurons against toxicity following 24 h exposure to 10 µM Aβ 1–42 (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These undesirable side effects of tamoxifen, along with numerous obstacles to the successful delivery of the drug to the tumor site, require the development of a targeted delivery system that grants site-specific delivery of the drug while minimizing the nonspecific off-target effects. Accordingly, an array of nanoparticulate delivery systems have been explored for their efficacy to deliver tamoxifen to the tumor cells, such as nanospheres and nanoparticles comprising poly-caprolactone (Łukasiewicz et al, 2021 ; Chawla & Amiji, 2002 ; Villemson et al, 2006 ). The motive behind the use of such biocompatible and biodegradable polymeric nanocarriers is to augment the selective delivery of drug dose to tumor site while sparing healthy tissues from drug’s off-target effect.…”
Section: Introductionmentioning
confidence: 99%
“…for their efficacy to deliver tamoxifen to the tumor cells, such as nanospheres and nanoparticles comprising polycaprolactone (Łukasiewicz et al, 2021;Chawla & Amiji, 2002;Villemson et al, 2006). The motive behind the use of such biocompatible and biodegradable polymeric nanocarriers is to augment the selective delivery of drug dose to tumor site while sparing healthy tissues from drug's off-target effect.…”
Section: Introductionmentioning
confidence: 99%